Henry Care: Journalism and Numeracy before the Field. Issue 2 (3rd April 2022) - Harrison, Steve
ABSTRACT: The concept of the journalistic field as developed by Pierre Bourdieu and his collaborators has proved fruitful for media theorists. The present article arose out of considerations linking field theory—and its associated concepts of habitus and symbolic capital—to the low regard in which journalists often appear to hold numeracy. Its focus is Henry Care, a writer and polemicist active in the United Kingdom in the 1670s and 1680s whose works included a popular self-help guide to numeracy and basic arithmetic. Because he was writing prior to the establishment of the journalistic field, Care gives historians an insight into how journalism could have developed along a different path, one in which the profession valued numeracy as highly as it does literary ability. Care's background as a news writer and pamphleteer was no bar to the popularity of his guide, and it is argued that the low value that journalism places on numeracy today is historically contingent rather than inevitable. Previously overlooked internal evidence provides fresh insight into the composition of Care's self-help guide.